Reducing Negative Attitudes Toward Immigrants in Russia and Taiwan: Possible Beneficial Effects of Naïve Dialecticism and an Incremental Worldview - Lee, I-Ching; Permyakova, Tatyana; Sheveleva, Marina (Frontiers in Psychology, 2020)
Greater mobility in human societies has resulted in more interactions and contact with immigrants. In the current research, we investigated how viewing the world as flexible, changing, and paradoxical (i.e., naïve dialecticism and an incremental theory) may predict one's authoritarian beliefs and in turn predict one's attitudes towards immigrants. To test the generalizability of our findings, we recruit comparable samples (i.e., college students) from two societies that are largely different (Russia and Taiwan). Great cultural similarities were observed. Naïve dialecticism and an incremental theory appeared as two distinctive constructs. People who were higher on naïve dialecticism and an incremental over entity theory had lower support for authoritarian beliefs (i.e., right-wing authoritarianism and social dominance orientation) and, in turn, had more favorable attitudes towards immigrants. Some cultural differences were also observed. Taiwanese participants' negative attitudes towards immigrants were entirely ideology-based, whereas Russian participants' negative attitudes towards immigrants were partly based on presumably personal experiences. Pan-cultural and culturally specific mechanisms in predicting attitudes towards immigrants were further discussed and explored.